NMR structural study on the As-P-S glassy system - Santagneli, S. H.; Skripatchev, I.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Schneider, J. (Amer Chemical Soc, 2007)
Glasses having the composition As2S3(1-x)-P2S5(x) with x ranging from 0 to 0.7 have been investigated to determine the compositional effect on properties and local structure. Glass transition temperature (T,) decreases and molar volume (V,,) increases with an increase in P content. Using P-31 NMR, we measured the strength of the P-31-P-31 magnetic dipolar interaction in the glass samples and the AsPS4 crystallized phase. Based on these data, we observed the formation of the As2P2S8 network, which reflects an increase in the average coordination number and a decrease in the degree of rigidity.